Leptin G-2548A promoter polymorphism is associated with increased plasma leptin and BMI in Brazilian women - Hinuy,Hamilton M. (2008)
Variants in leptin gene (LEP) have been implicated in the pathogenesis of obesity. The relationship between LEP G-2548A polymorphism and obesity-related traits was evaluated in a sample of Brazilian women (n = 228) who were randomly selected from two clinical centers in Sao Paulo city. Blood samples were collected for DNA extraction, plasma leptin and serum lipids measurements. LEP G-2548A genotypes were identified by a PCR- RFLP strategy using the endonuclease Alw44I. LEP G-2548A was associated with obesity after adjustment for covariates (age, hypertension, coronary artery disease, smoking and physical activity). Women carrying G allele had a four times higher risk of obesity than the A allele carriers (OR: 4.11, CI95%: 1.06-15.90, p = 0.041). G allele was also related to increased plasma leptin (p = 0.024) and body mass index (p = 0.027). Hypertension, hyperglycemia, dyslipidemia and coronary artery disease were associated with obesity. However LEP G-2548A polymorphism was not related to these variables. All together these data suggest that LEP G-2548A polymorphism has an important role in regulating plasma leptin levels and body mass index in women.